O Google Earth™ como uma ferramenta de apoio aos estudos preliminares de geomorfologia fluvial: estudo de caso no riacho de Vila Maria – Garanhuns-PE - Oliveira, George Pereira de (2018)
The virtual globes are enabling a new way of seeing the planet Earth. For the geomorphologists these images are presented as a tool to analyze the landforms, to obtain data of landscape recognition or to measure, preliminarily, qualitative and quantitative variablesThis article aims to evaluate the potential of the Google Earth software in the analysis of fluvial channels from a qualitative environmental perspective of the Vila Maria stream, in the outskirts of the city of GaranhunsPE. This evaluation is based on the identification of the fluvial style of this creek. This one is a headwater streams, with partially confined valley, bed load with medium granulometry and course with tendency to straightness. A methodology allowed to obtain satisfactory preliminary results.